Replicate sequencing libraries are important for quantification of allelic imbalance - Asia Mendelevich (Nature Portfolio, 2021)
Allele-specific expression in diploid organisms can be quantified by RNA-seq and it is common practice to rely on a single library. Here, the authors show that the standard approach has variable error rate and present Qllelic as a tool to improve reproducibility of allele-specific RNA-seq analysis.